Introduction to potable water treatment processes. - Parsons, Simon, ....-; Jefferson, Bruce, ....- (Oxford : Blackwell, 2006)
The availability of a reliable supply of water is one of the most important determinants of human health, with the supply of clean drinking water being a multibillion dollar industry in the developed world and a key concern for less developed countries. Introduction to Potable Water Treatment Processes illustrates the link between raw water quality and treatment process selection and performance. Individual chapters concentrate on specific water treatment processes, detailing the chemical and engineering principles behind the process, and further illustrating process implementation by the use of process flow diagrams, photographs and case studies. The final three chapters look specifically at the removal of organic and inorganic contaminants and at the treatment and disposal of sludge. With introductory chapters covering both UK/European legislation and WHO guidance, and a general introduction to process flow diagrams, Introduction to Potable Water Treatment Processes is essential reading for anyone operating or managing a water treatment process, or carrying out research on water treatment processes.
Keywords: Drinkwaterzuivering